Elkanah Billings: The Lawyer Who Revealed the Ancient Life of the Past - Minicucci, Jeffrey M. (Geoscience Canada, 2016)
Elkanah Billings is an important, historical example of a 19th century Ontario lawyer who made a contribution to Canadian life by engaging in a pursuit outside the practice of law. An accomplished autodidact (i.e. a self-taught expert) and renowned as the father of Canadian paleontology, Billings has the distinction of being claimed by the global paleontological and geological professional communities, and by the Ontario legal profession. Although some researchers have alleged that Billings had abused alcohol during his life, he nonetheless managed to establish a remarkable career as a paleontologist. He applied the researching, analytical, and argumentative skills that he had acquired during his years of training and practice as a lawyer to the science of paleontology enabling him to peel back the layers of time to reveal the ancient life of the past. In view of his strengths, weaknesses, and professional accomplishments, the example of Billings’ history potentially becomes increasingly relevant in the effort to reinforce the importance of ethics and professional responsibility among earth science and evolutionary biology professionals and to promote a shared sense of professional community and heritage. The example of Billings’ history also presents a golden opportunity for the synthesist to nurture a closer connection between the law and science in the form of interdisciplinary or multidisciplinary dialogue and collaboration. RÉSUMÉ Elkanah Billings est un important exemple historique d’un avocat Ontarienne du XIXe siècle qui a apporté une contribution à la vie Canadienne en se livrant à une poursuite en dehors de la pratique du droit. Autodidacte accompli et reconnu comme le père de la paléontologie canadienne, Billings a la paricularité d’être revendiqué par les communautés professionnelles paléontologiques et géologiques mondiales, et par la profession juridique de l’Ontario. Bien que certains chercheurs ont affirmé que Billings avait abusé de l’alcool au cours de sa vie, il a réussi néanmoins à établir une carrière remarquable en tant que paléontologue. Il a appliqué la recherche, d’analyse, et les compétences argumentatives qu’il avait acquises au cours de ses années de formation et de pratique comme avocat à la science de la paléontologie qui lui permet de décoller les couches de temps pour révéler l’ancienne vie du passé. Compte tenu de ses points forts, les faiblesses et les réalisations professionnelles, l’exemple de l’histoire Billings devient potentiellement plus pertinent dans les efforts visant à renforcer l’importance de l’éthique et de la responsabilité professionnelle des sciences de la terre et les professionnels de la biologie de l’évolution et de promouvoir un sens partagé de la communauté professionnelle et le patrimoine. L’exemple de l’histoire Billings présente également une occasion en or pour le synthésiste d’entretenir un lien plus étroit entre la loi et la science sous la forme de dialogue et de collaboration interdisciplinaire ou multidisciplinaire.